Interactions Between Computational Intelligence and Mathematics Part 2 - Kóczy, László T.; Medina-Moreno, Jesús; Ramírez-Poussa, Eloísa; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents recent research in the field of interaction between computational intelligence and mathematics. In the current technological age, we face the challenges of tackling very complex problems - in the usual sense, but also in the mathematical and theoretical computer science sense. However, even the most up-to-date results in mathematics, are unable to provide exact solutions of such problems, and no further technical advances will ever make it possible to find general and exact solutions. Constantly developing technologies (including social technologies) necessitate handling very complex problems. This has led to a search for acceptably "good" or precise solutions, which can be achieved by the combination of traditional mathematical techniques and computational intelligence tools, in order to solve the various problems emerging in many different areas to a satisfactory degree. Important funding programs, such as the European Commission's current framework programme for research and innovation - Horizon 2020 - are devoted to the development of new instruments to deal with the current challenges. Without doubt, research topics associated with the interactions between computational intelligence and traditional mathematics play a key role. Presenting contributions from engineers, scientists and mathematicians, this book offers a series of novel solutions for meaningful and real-world problems that connect those research areas.
Chapter 1. On the incorporation of interval-valued fuzzy sets into the Bousi-Prolog system: declarative semantics, implementation and applications (Clemente Rubio-Manzano) -- Chapter 2. The existence of generalized inverses of fuzzy matrices (Miroslav Ciric) -- Chapter 3. Gender Detection of Twitter Users based on Multiple Information Sources (Marco Vicente) -- Chapter 4. On the n-ary generalization of dual bonds (Ondrej Krídlo) etc.
Keywords: Computational intelligence; Artificial intelligence; Mathematics -- Data processing; Computational Intelligence; Artificial Intelligence; Computational Science and Engineering